2006
DOI: 10.1164/rccm.200604-547oc
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Annular Displacement Predicts Survival in Pulmonary Hypertension

Abstract: TAPSE powerfully reflects RV function and prognosis in PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
718
3
32

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 979 publications
(786 citation statements)
references
References 28 publications
22
718
3
32
Order By: Relevance
“…These results were supported by comparable results for cardiovascular mortality in addition to correlations between RVEF and previously reported robust predictors of outcome in PAH, including cardiac index, right atrial pressure, TAPSE, NT-proBNP and SvO 2 [4,[20][21][22]. Collectively, these observations suggest measurement of RVEF may be a useful tool to evaluate the long-term prognosis of patients with PAH.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results were supported by comparable results for cardiovascular mortality in addition to correlations between RVEF and previously reported robust predictors of outcome in PAH, including cardiac index, right atrial pressure, TAPSE, NT-proBNP and SvO 2 [4,[20][21][22]. Collectively, these observations suggest measurement of RVEF may be a useful tool to evaluate the long-term prognosis of patients with PAH.…”
Section: Discussionsupporting
confidence: 84%
“…Other baseline variables relating to the RV function have previously been associated with overall survival in patients with PAH. Echocardiographic measurement of TAPSE at baseline predicted survival in a heterogeneous population of patients with precapillary PH (only one-third of whom had idiopathic PAH) [21]. Similarly, RVEF assessed with cardiac MRI independently predicted long-term outcome in patients with PAH [22].…”
Section: Discussionmentioning
confidence: 99%
“…4 A TAPSE of \ 1.8 cm predicted a SVI of \ 29 mLÁm -2 . 1 We found a modest correlation between TAPSE by M mode and SV (r = 0.48).…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, RV dysfunction assessed using RV ejection fraction (RVEF), RV stroke work, RV fractional area of change, or tricuspid annular systolic plane excursion (TAPSE) is a predictor of outcome in cardiac surgery, transplantation, and patients with pulmonary hypertension. [1][2][3] Due to its simplicity and ease of application, TAPSE has become a commonly measured variable in the assessment of RV function, however, it remains one dimensional. Tricuspid annular systolic plane excursion is commonly measured using M mode, but it can be measured using speckle tracking (tracking of B mode markers) or tissue tracking (TT) [integrating annular velocity (S') measured by colour tissue Doppler].…”
Section: Résumémentioning
confidence: 99%
“…[36][37][38][39] RV longitudinal shortening (tricuspid annular plane excursion [TAPSE]) and transverse shortening provide clinical relevant measures that are correlated with global RV function. 22,40,41 Although the determination of global measures of RV function is relative time consuming, these measures are simpler to obtain. Mauritz et al 22 showed that both transverse and longitudinal shortening were valuable parameters and that, in particular, a progressive decrease in RV transverse wall motion is associated with end-stage RV disease.…”
Section: Regional Rv Function and Strainmentioning
confidence: 99%